Relationship between parental emotional styles and family values to anxiety level among primary school children - Ab Ghaffar, Siti Fatimah; Ahmad, Ghazali; Ibrahim, Mazne; Mat Yussof, Nur Dalila; Muhammad, Nur Hafizah; Musa, Ramli; Mohamad Isa, Irma Izani (UPM Press, 2023)
Introduction: Childhood anxiety is one of the common mental health problems in children. Untreated childhood anxiety will lead to a higher risk of developing mental health problems in adulthood. Thus, this study aimed to investigate the relationship between parental emotional styles and family values to anxiety level among primary school children. Methods: A cross-sectional study was conducted in a selected primary school in Kelantan, Malaysia. A set of questionnaires consisted of the Revised Child Anxiety and Depression Scale–Parents’ Report (RCADS-P 25), the Parental Emotional Style Questionnaire (PESQ), and the Asian Family Characteristics Scale (AFCS) was used for assessing anxiety, parental emotional styles, and family values, respectively. Data were collected via an online survey using Google Form, and were analysed using Multiple Linear Regression (MLR) to determine the factors associated with childhood anxiety. The significance value was set at p < 0.05. Results: A total of 150 parents of primary school children from the selected school was involved in this study. The majority of respondents were females (82.0%), married (94.7%), hold a degree (66.7%), and were working in the government sector (60.0%). Most of the respondents’ child were twelve years old (20.7%) and males (62%). Based on the MLR, emotional dismissing parental style (p = 0.025) and family values (p = 0.016) were significantly associated with anxiety in these children. Conclusion: Emotional dismissing parental style and family values were significant predictors of anxiety in primary school children. Future intervention research on childhood anxiety is needed.